SOSIALISASI PENINGKATAN PENDAPATAN BAGI ANGGOTA KOPERASI SANTIKA JAYA DASAN SARI KELURAHAN KEBUN SARI KOTA MATARAM - Muhamad Sayuti; Mimi Cahayani; Titin Windiasari (Nusantara Hasana Journal, 2025)
Cooperatives, as people's economic institutions, play a strategic role in supporting community economic independence. However, many cooperatives are still not optimal in improving the welfare of their members. This community service activity aims to increase the capacity of members of the Santika Jaya Dasan Sari Cooperative in terms of increasing income through entrepreneurship training, simple financial management, and digital marketing. The implementation method consists of lectures, discussions, and simulations. Evaluation is carried out through pre- and post-tests, as well as direct observation. The results show an increase in the knowledge and skills of cooperative members in managing their businesses and conducting promotions. This outreach has a positive impact on building awareness and motivation of cooperative members to become more productive entrepreneurs.